Faktor-Faktor yang Mempengaruhi Kerawanan dan Ketahanan Pangan dan Implikasi Kebijakannya di Kabupaten Rembang - Nugroho Indira Hapsari; Iwan Rudiarto (Jurnal Wilayah dan Lingkungan, 2017)
Food security issue remains a worldwide concern and discussed in the main point of Millennium Development Goals (MDGs) and Sustainable Development Goals (SDGs) documents. Several problems threatening food security in addition to socioeconomic issue and the decline of agricultural land are the decrease of agricultural production caused by climate change. The Indonesian Government has proposed Food Security and Vulnerability Atlas (FSVA) to find out areas which require prioritized handling on food insecurity in order to determine appropriate policy strategy. Even though the result of FSVA 2015 concluded food security status in Rembang District, it does not guarantee similar condition in the villages. To complement the result of FSVA, this research attempts to identify food security and food insecurity at the village level by using spatial analysis and statistical analysis with factor analysis in order to examine the cause of food security and food insecurity. The result showed that most villages in Rembang fell into sufficient food security status (105 villages) and food security status (90 villages), but there remained 10 villages left into an extremely food insecurity status which required more attention. The result of factor analysis showed the main factor causing food security was food availability and the main factor of food insecurity was socioeconomic factors. Food security strategies and policies were determined by indicators which constructed factor grouping that affected food security and food insecurity. This strategy was not only to solve food insecurity problems but also to increase food security in Rembang.